2021
DOI: 10.1177/0739456x211051420
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Planning: Views from Management Consultants

Abstract: Professional planners working in the private sector intersect with a complex sphere of business interests. Management consultants have a growing influence in many organizations, including private sector planning firms. Using a mixed-method approach to examine the strategies and priorities of management consultants, I find that management consultants view the “value” of planning as opening the door to future contracts and selling firm services. This has implications for understanding how practitioners reconcile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…However, this article does not examine the normative questions surrounding when a consultant should be employed for strategy implementation. Indeed, implementation success in this study is viewed through an efficiency prism-sidestepping criticism that management consultants may exploit client vulnerabilities, increase the marketization of the public sector, facilitate service reviews that lead to reduction in public services, and promote the overreliance on metrics and analytics that can ignore local context (Linovski, 2021). While these concerns are paramount to the appropriate and just delivery of public services and should not be taken lightly, one can also seek to understand how best to employ management consultants for public objectives so that government resources are not squandered.…”
Section: Discussionmentioning
confidence: 99%
“…However, this article does not examine the normative questions surrounding when a consultant should be employed for strategy implementation. Indeed, implementation success in this study is viewed through an efficiency prism-sidestepping criticism that management consultants may exploit client vulnerabilities, increase the marketization of the public sector, facilitate service reviews that lead to reduction in public services, and promote the overreliance on metrics and analytics that can ignore local context (Linovski, 2021). While these concerns are paramount to the appropriate and just delivery of public services and should not be taken lightly, one can also seek to understand how best to employ management consultants for public objectives so that government resources are not squandered.…”
Section: Discussionmentioning
confidence: 99%
“…Nearly half of all planners work for private companies (Raco, 2018). As recent research has shown, their activities are often focused on market-building and profit-making rather than the establishment and delivery of public interest projects (Linovski, 2021). Moreover, the growing influence of private sector involvement in the delivery of planning programmes and, in particular, the greater reliance on private finance for new projects, has given financial actors and knowledge practices a much stronger role in the building and governance of cities (Penny, 2021).…”
Section: The Development Of Reflexive Forms Of Practice and Knowledge...mentioning
confidence: 99%